Circulating level of CD4+ CD25+ FOXP3+ T cells in patients with chronic urticaria. (14th October 2014) - Arshi, Saba; Babaie, Delara; Nabavi, Mohammad; Tebianian, Majid; Ghalehbaghi, Babak; Jalali, Farhad; Ahmadvand, Alireza; Gholami, Reza
Abstract Background CD4+ CD25+ T‐regulatory (Treg) cells play critical roles in maintaining peripheral tolerance and preventing autoimmunity. As characteristics of Treg cells have not been precisely investigated in chronic urticaria (CU) yet, this study was performed. Objective To determine the frequencies of circulating CD4+ CD25+ FOXP3+ T cells and serum levels of interleukin (IL)‐10, transforming growth factor (TGF)‐β, and IL‐17 in patients with chronic autoimmune urticaria and chronic idiopathic urticaria compared to healthy controls. Methods Peripheral blood mononuclear cells (PBMCs) were obtained from patients with CU and healthy controls. The frequency of CD4+ CD25+ T cells in PBMCs and expression levels of FOXP3 were detected by flow cytometry. The serum levels of IL‐10, TGF‐β, and IL‐17 were measured by enzyme‐linked immunosorbent assay. Results A significant decrease in the percentage of circulating CD4+ CD25+ FOXP3+ T cells was detected in patients with CU, compared to control subjects. However, no significant difference was detected on the serum levels of IL‐10, TGF‐β, and IL‐17 between patients with CU and control subjects. Conclusions This study demonstrated that the frequency of Treg cells in PBMCs was decreased in patients with CU. Further studies are needed to clarify the exact role of Treg cells in the pathogenesis of CU and factors regulating their function.